FROM INCULCATING ISLAMIC VALUES TO ‘RAHMATAN-LIL-ALAMIN’: PROMULGATING VARIOUS APPROACHES OF ISLAM IN MALAYSIA - Zamri bin Ahmad, Abdul Mua’ti (Journal of Malay Islamic Studies, 2019)
The government of Malaysia has introduced ‘Inculcating Islamic Values’ during the reign of Prime Minister Dr Mahathir in the 80s, ‘Civilizational Islam (Islam Hadhari)’ during the reign of Prime Minister Abdullah Badawi in 2004, ‘Wasatiyah’ during the reign of Prime Minister Najib Razak in 2010 and ‘Rahmatan-lil-Alamin’ recently in 2018 under the new government. All the approaches were designed towards developing a modern society in predominantly Malay-Muslim society of Malaysia. The concepts were normally publicized as a part of the manifesto during the political campaigns prior to the general elections. Since then, Malaysians, Muslims and non-Muslims alike were expecting to observe more detail explanations of the concepts and how it could be translated into actions in the multi-religion society. Occasionally the Prime Minister will reiterate the approaches and spell out in detail the methods of implementing the concept or to translate the concepts into policies. The concepts will further be elaborated in a couple more speeches delivered by the Prime Minister and senior ministers including the information minister. The mainstream media has also allotted special columns and programs to outspread the concepts even though at times not in detail and lack of continuity. Today, after about one year since the latest concept (Rahmatan-lil-alamin) has been conceived, what are the peoples’ perceptions towards it? Do the people really made to understand the concept? To what extent has the media been used to disseminate the idea? This paper will discuss the analysis of the dissemination of the concept through the main stream media in Malaysia.